1971
DOI: 10.1111/j.1365-2621.1971.tb03308.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipids of Cured Centennial Sweet Potatoes

Abstract: Lipids isolated from cured Centennial sweet potatoes were identified and quantitated by a combination of column and thin layer chromatography. These lipids were shown to consist of 42.1% neutral lipids, 30.8% glycolipids and 27.1% phospholipids. Triglycerides and steryl esters were the major lipids of the neutral fraction. Among the phospholipids, phosphatidyl ethanolamine, phosphatidyl choline end phosphatidyl inositol were the most abundant, Galactolipids and the steryl glucosides were also present, The pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Thus, the data given in Table 2 represent typical glycolipid contents of commercial plant foodstuffs available in Japan from summer to winter. However, the present data compare well with those of previous studies (3)(4)(5)(6)(7)(8)(9)(10) in light of probable differences in cultivar, locality, and harvest time of plants. The HPLC-ELSD condition as described here seems useful for the quantitation of plant glycolipids.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the data given in Table 2 represent typical glycolipid contents of commercial plant foodstuffs available in Japan from summer to winter. However, the present data compare well with those of previous studies (3)(4)(5)(6)(7)(8)(9)(10) in light of probable differences in cultivar, locality, and harvest time of plants. The HPLC-ELSD condition as described here seems useful for the quantitation of plant glycolipids.…”
Section: Discussionsupporting
confidence: 90%
“…These glycolipids are widely distributed in edible plants such as cereals, legumes, vegetables, and fruits (1,2). In previous studies (3)(4)(5)(6)(7)(8)(9)(10), plant glycolipids have been quantified gravimetrically or colorimetrically after separating and isolating them with column chromatography or with thin-layer chromatography (TLC); however, these techniques are time-consuming and labor intensive.…”
mentioning
confidence: 99%
“…In the work reported here, neutral lipids were found to be the most abundant at 48.1%, followed by glycolipids, 31.2% and phospholipids, 20.7%. Walter et al (1971) reported 42.1%, 30.8%, and 27.1% for the same fractions. Over 98% of the lipid sample to be chromatographed was recovered from the column.…”
Section: Preparation Of Methyl Esters Of Long Chain Fatty Acidsmentioning
confidence: 82%
“…Total lipids of pureed raw, Centenntial sweet potatoes, were found to be 2.45% on a dry weight basis. Walter et al (1971) reported 2.7% and Boggess et al (1967Boggess et al ( , 1970 1.6% total lipids. In the work reported here, neutral lipids were found to be the most abundant at 48.1%, followed by glycolipids, 31.2% and phospholipids, 20.7%.…”
Section: Preparation Of Methyl Esters Of Long Chain Fatty Acidsmentioning
confidence: 94%
“…The glycolipids exhibited a relatively high proportion of linolenic acid (183). The lipid composition in Dioscorea tubers appears in general very similar to that in many nonphotosynthetic plant storage tissues containing little fat such as sugar beet (Beiss, 1969), sweet potato (Walter et al, 1971), the Irish potato (Galliard, 19681, and Alocasia macrorrhiza tubers (Opute and Osagie, 1978). Since the diet is virtually carbohydrate based, the amount of essential fatty acid supplied from yam sources may be critical (Sonderhjelm et al, 1971).…”
Section: Resultsmentioning
confidence: 99%